SIGNIFICANCE OF CYTOKINES IN THE DEVELOPMENT OF LIVER DISEASES - Malika Khusanovna Tolibjonova; Tursunkulova Roxat Baxtiyorovna (Web of Journals Publishing, 2025)
“The role of the cytokines in chronic liver disease” Various cytokines play a huge role in the regulation of fibrogenesis. Cytokines are low molecular weight proteins that are produced and secreted mainly by activated cells of the immune system and are involved in the development of immune responses according to the cellular or humoral type. Produced transiently, they have a short half-life and act at very low concentrations by binding to high affinity receptors on the surface of target cells.
Keywords: Chronic liver diseases, immune inflammatory response, damage to hepatocytes, therapy